Self-Directed Learning Based Teaching Module on Angle Material - Via Yustitia; Dian Kusmaharti; Eldine Salsabila Putri (LPPM Undiksha, 2024)
The change of curriculum to an independent curriculum was motivated by the backwardness of learning. In its implementation, the independent curriculum is not based on the concept set by the government. Teaching modules need to be developed so that they can be used to facilitate teachers and students. This research is a development research (R&D). This study aims to develop a self-directed learning (SDL) teaching module and test the feasibility of the SDL teaching module. In developing the teaching module, the researcher used the 4D research model. Data collection used documentation, observation, unstructured interviews and questionnaires. Data analysis used quantitative descriptive analysis techniques. Based on the research that has been done, the researcher produced an SDL teaching module. The modified 4D model development process developed the process of developing the teaching module. The developed teaching module was categorized as very suitable for use in learning and has been proven theoretically and empirically. The SDL teaching module that has been developed can facilitate teachers and students in implementing learning that is in line with the concept of the independent curriculum.